Prasenā, Prasīnā & Prasannā: The Evidence of the Niśvāsaguhya and the Tantrasadbhāva - Somadeva Vasudeva (Ksiegarnia Akademicka Publishing, 2021)
Prasenā, Prasīnā & Prasannā: The Evidence of the Niśvāsaguhya and the Tantrasadbhāva